2015
DOI: 10.11114/jets.v3i6.1055
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-cultural Comparative Study of Uses and Perceptions of Technology in Education among Turkish and US Undergraduates

Abstract: The purpose of this study was to investigate differences and similarities among United States (US) and Turkish university students in technology ownership, uses of technology for academic purposes, perceived importance of technology, and preferences for technology in education. The EDUCAUSE Center for Analytics and Research (ECAR) undergraduate student technology survey was used to collect data from Turkish students (N=384) at Abant Izzet Baysal University and US students (N=399) at Louisiana State University … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
1
3
0
1
Order By: Relevance
“…In addition, the Israeli students perceived collaborative spaces as highly useful in their academic work, while the Australians perceived the library e-journals and scholarly websites as highly useful. In line with previous studies (He & Li, 2019;Kittler, Rygl, & Mackinnon, 2011;Tekinarslan et al, 2015), these findings still required further explanation. While the Australian students found official academic resources and practices more beneficial to their academic learning, the Israeli students tended to consider the external collaborative resources and practices more helpful.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In addition, the Israeli students perceived collaborative spaces as highly useful in their academic work, while the Australians perceived the library e-journals and scholarly websites as highly useful. In line with previous studies (He & Li, 2019;Kittler, Rygl, & Mackinnon, 2011;Tekinarslan et al, 2015), these findings still required further explanation. While the Australian students found official academic resources and practices more beneficial to their academic learning, the Israeli students tended to consider the external collaborative resources and practices more helpful.…”
Section: Discussionsupporting
confidence: 82%
“…Specifically, cultural values affect information and communication technology (ICT) adoption in formal learning settings (Arenas‐Gaitán et al, 2011). Several researchers have reported differences in students' attitudes to and perceptions of technology in different cultures (Li & Kirkup, 2007; Tekinarslan et al, 2015). Tekinarslan et al (2015), for example, found that a LMS, web‐based bibliography tools, and freely available course content beyond the campus were more important for American students than Turkish students.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The education systems, one of the areas impacted in this change and development process, have made a great breakthrough with technology (Çolak et al, 2023). In this day and age, the technology in question has become an important identifier of national and global as well as cultural borders (Tekinarslan et al, 2015). As far as the historical perspective of technology is concerned, it is possible to say that since the beginning of mankind, activities such as production as a whole, and developing and inventing tools and gadgets in order to dominate and govern nature have endured (Yörükoğulları, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Ulusal ve hatta kültürel sınırları yeniden tanımlayan teknoloji kavramı yaşamımızda önemli bir yere sahiptir (Tekinarslan, Kennedy & Nicolle, 2015). Bu denli büyük etkiye sahip olan teknoloji kavramıyla ilgili alanyazındaki bazı tanımlar incelenmiştir.…”
Section: Introductionunclassified